"Peruvian balsam": an example of transoceanic transfer of medicinal knowledge - Angela Schottenhammer (BMC, 2020)
Abstract Background Connections between China and the new Spanish colonies in America are known for an exchange of silver for silks and porcelains. That also medicinal drugs and medicinal knowledge crossed the Pacific Ocean is hardly known or discussed. Myroxylon balsamum (L.) Harms var. pereirae (Royle) Harms ("New World" or "Peruvian balsam") is a botanical balsam that has a long history of medicinal use, particularly as antiseptic and for wound healing. Except for a Chinese article discussing the reception of balsam in China and Japan, no scientific studies on its impact in China and Japan and the channels of transfer from the Americas to Asia exist. Methods Description: (1) This section provides a general introduction into Commiphora gileadensis ("Old World" balsam) as a medicinal category and discusses the specific medicinal properties of Myroxylon balsamum (L.) Harms var. pereirae (Royle) Harms. The section "Historical research and uses" provides a brief survey on some historical analyses of balsam. Aim, design, setting: (2) Applying a comparative textual and archaeological analysis the article critically examines Chinese and Japanese sources (texts, maps) to show (i) what Chinese and Japanese scholars knew about balsam, (ii) where and how it was used, and (iii) to identify reasons why the "digestion" of knowledge on balsam as a medicinal developed so differently in China and Japan. Results and discussion This chapter discusses the introduction of "Peruvian balsam" into, its uses as a medicinal as well as its scholarly reception in early modern China and Japan and introduces the channels of transmission from Spanish America to Asia. It is shown that Myroxylon balsamum (L.) Harms var. pereirae (Royle) Harms was partly a highly valued substance imported from the Americas into China and Japan. But the history of the reception of medicinal knowledge on Peruvian balsam was significantly different in China and Japan. Conclusions In Japan, the knowledge on Myroxylon balsamum was continuously updated, especially through mediation of Dutch physicians; Japanese scholars, doctors and pharmacists possessed a solid knowledge on this balsam, its origin and its medicinal uses. In China, on the contrary, there was no further "digestion" or development of the knowledge on either Myroxylon balsamum (L.) Harms var. pereirae (Royle) Harms or Commiphora gileadensis. By the late nineteenth century, related medicinal and even geographic knowledge had mostly been lost. The interest in "balsam" in late Qing scholarship was pure encyclopaedic and philosophic.